Needs and Content Concept Analysis of Local Wisdom–Based Digital Supplementary Teaching Materials for Environmental Awareness in Bajulan Village, Nganjuk - Martha Abymanyu Ragil Atmaja; Sumarmi Sumarmi; Tuti Mutia (STKIP Singkawang, 2026)
Digital transformation in education requires learning innovations that are not only technology-oriented but also integrate local cultural values. This study aims to analyse needs and design a concept for digital teaching materials based on the local wisdom of the Bajulan Traditional Village, Nganjuk. This study employs a qualitative approach supported by simple quantitative data. The research subjects included teachers and class XI Geography students at SMAN 3 Nganjuk, as well as traditional leaders from Bajulan Village as supporting informants. Qualitative data was obtained through observation, interviews, and curriculum analysis, whilst quantitative data was obtained through questionnaires analysed using percentages. The results of the study indicate that teachers and students require digital teaching materials that are more interactive, contextual, and relevant to daily life, as the media currently in use are considered unengaging. Content analysis indicates that ATP 1.1–1.2 still emphasise environmental concepts in a theoretical manner, whilst ATP 1.3–1.5 have the potential to be integrated with local wisdom values such as sowan punden, ruwat sumber, and bersih desa. The integration of local wisdom into digital teaching materials has the potential to strengthen students’ understanding of geographical concepts, enhance environmental awareness, and foster a love for local culture.